High-affinity multivalent wheat germ agglutinin ligands by one-pot click reaction - Beckmann, Henning S G (Beilstein-Institut, 2012)
A series of six mono-, di-, and trivalent N,N’-diacetylchitobiose derivatives was conveniently prepared by employing a one-pot procedure for Cu(II)-catalyzed diazo transfer and Cu(I)-catalyzed azide–alkyne cycloaddition (CuAAC) starting from commercially available amines. These glycoclusters were probed for their binding potencies to the plant lectin wheat germ agglutinin (WGA) from Triticum vulgaris by an enzyme-linked lectin assay (ELLA) employing covalently immobilized N-acetylglucosamine (GlcNAc) as a reference ligand. IC(50) values were in the low micromolar/high nanomolar range, depending on the linker between the two disaccharides. Binding enhancements β up to 1000 for the divalent ligands and 2800 for a trivalent WGA ligand, compared to N,N’-diacetylchitobiose as the corresponding monovalent ligand, were observed. Molecular modeling studies, in which the chitobiose moieties were fitted into crystallographically determined binding sites of WGA, correlate the binding enhancements of the multivalent ligands with their ability to bind to the protein in a chelating mode. The best WGA ligand is a trivalent cluster with an IC(50) value of 220 nM. Calculated per mol of contained chitobiose, this is the best WGA ligand known so far.